Seroprevalence of Cytomegalovirus Antibodies among Blood Donors in Aminu Kano Teaching Hospital, Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Transfusion transmissible infections (TTIs) may potentially lead to serious harm to recipients of blood transfusion. Cytomegalovirus (CMV) can be transmitted through blood transfusion, and its impact is the most severe among immunocompromised recipients. Its transmission can be reduced through screening of blood donors, blood and blood products for CMV antibodies, leuco-depletion or pathogen inactivation.Objective:This was a cross-sectional study conducted among 250 blood donors between October and December 2012 in Aminu Kano Teaching Hospital, Kano, Nigeria. To determine the prevalence of human immunodeficiency virus (HIV) I and II antibodies, HBsAg, hepatitis C virus (HCV) antibodies, syphilis and anti-CMV IgM and IgG antibodies. In addition, the type of donation and donation patterns were also assessed.Materials and Methods:Five milliliters were collected from the participants. One milliliter was dispensed into ethylenediaminetetraacetic acid (EDTA) container and mixed gently, the remaining 4 ml were dispensed into a plain bottle and was centrifuged; serum obtained was divided into two one was stored at − 20°C which was later used to test for the anti-CMV IgG/IgM antibodies, whereas the other portion was used for routine screening of TTIs. The EDTA sample was used to assess haemoglobin concentration. An interviewer administered simplified questionnaire was used to obtain information on demographic and other variables related to donation habits. Association between the socio-demographic characteristics of the blood donors and the anti-CMV antibodies was analysed. Similarly, association between the anti-CMV antibodies and the other routinely screened TTIs was assessed. Results were tested for evidence of statistical association.Results:Majority of the blood donors were males 242 (96.8%). One hundred and seven (42.6%) of the blood donors were within the age group of 25–34 years. Only 10.8% of the donors were voluntary donors whereas the remaining were family replacement donors. Prevalence rates of 100% and 4.4% were found for anti-CMV IgG and anti-CMV IgM antibodies, respectively. HBsAg, HIV I/II, anti-HCV antibodies and syphilis were prevalent in 6.8%, 1.2%, 0.8% and 0% of the donors, respectively.Conclusion:Seroprevalence of anti-CMV IgG and anti-CMV IgM antibodies among blood donors in this study was found to be 100% and 4.4%, respectively. Therefore, routine predonation screening for anti-CMV antibodies may not be cost effective. Leucocyte depletion and pathogen inactivation methods are better options. However, these can better be achieved when centralized system of blood transfusion is adopted. Therefore, there is a need to enhance the functional capacity of our national blood transfusion service.